Detained change? Negative prescriptive stereotypes and cognitive gender schemas of polish female students - Paprzycka, Emilia; Mianowska, Edyta; Walentynowicz-Moryl, Katarzyna (Adult Education Discourses, 2022)
This article addresses the topic of negative prescriptive stereotypes of femininity and masculinity, and cognitive gender schemas of young women. The aim of the research performed was to identify definitions of non-femininity and non-masculinity and to explore the gender identity of young female students. The study sought to answer the following questions: What are their individual gender identities, and how are these identities related to definitions of non-femininity and non-masculinity? The study surveyed a representative sample of 1152 randomly selected student women using the standardized ‘Inventory for the Assessment of Psychological Gender’, an instrument based on the Bem Sex Role Inventory. Analysis revealed that the most common individual gender identities identified were androgynous and definite schemas. These schemas diversify definitions of non-femininity and non-masculinity. When defining non-femininity, women using masculine and indefinite schemas were more likely than androgynous and feminine women to reject the distinction between feminine and masculine characteristics.